Effect of cyclic loading on failure of canal embankment on soft clay deposit - Tanawoot Kongsung; Chao, Kuo Chieh; Avirut Puttiwongrak; Krit Saowiang; Royal Thai Government Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2022)
The road embankments along irrigation canals in the lower Chao Phraya plain have been rehabilitated in recent decades to accommodate the increased traffic volume caused by land expansion. After that, embankment failure occurs, and a recent study speculated that the sudden drawdown event is one of the important factors impacting embankment stability. Several studies have emphasized the importance of evaluating cyclic loads, which can cause road embankment failure. Because vehicle speed and vibration will have a significant impact on the subgrade soil, it is necessary to investigate and address the behavior of soft soil foundations under cyclic loading circumstances produced by traffic. Cyclic loading can cause embankment failure due to the cumulative effect of strain and elevated pore water pressure. As a result, the impact of cyclic stress from traffic loads and threshold stress on embankment stability must be measured, and the behavior of soft soils must be investigated. In addition, the sample and field survey were conducted along the Rapeepat canal embankment on the local road PT.5021 between sta.17+300 and 17+750 m, with laboratory tests conducted at the Asian Institute of Technology. Triaxial testing was performed with a normally-consolidation ratio of unity and cyclic triaxial testing with varied cyclic stress 23,50, and 98 kPa. and frequencies of 1.50 Hz and 2.50 Hz to cover the vehicle's permitted speed on this country road based on the allowable level of service. The threshold stresses in each condition were determined, and the threshold stress of Bangkok soft clay was found to be roughly 73 percent to 75 percent of its maximal monotonic strength. The permanent axial strain and excessive pore water pressure of Bangkok soft clay evolved over time in all of the trials. Furthermore, using PLAXIS-2D, a numerical traffic loading simulation was built to investigate the soft Bangkok clay behavior under cyclic vehicle loads and compare the results to experimental results. Finally, the numerical analysis revealed that the amplitude of cyclic stress distribution, load frequency, and soft clay thickness all had an impact on the formation of permanent strain and excess pore water pressure. As a result, there is a significant agreement between the validation of cyclic triaxial results and numerical data. When CSR< 0.73, the mobilization of permanent axial strain and excess pore water pressure occurs rapidly in the first few cycles, then both characteristics stabilize with time. The soil will fluidize in a limited number of cycles if CSR {u2265}0.73. As a result, the soft Bangkok clay threshold stress was used to predict the embankment stability of the rural road embankment along the irrigational canal on the soft Bangkok clay foundation, which is an important consideration. To summarize, traffic loads can reduce embankment stability, whereas embankment failure can be caused by a combination of factors including fast drawdown, traffic loading, erosion, infiltration, and construction maintenance activities.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Geotechnical and Earth Resources Engineering
Thesis (M. Eng.) - Asian Institute of Technology, 2022
Keywords: Embankments Roads -- Thailand -- Lower Chao Phraya; Clay -- Thailand -- Lower Chao Phraya; Geotechnical engineering -- Thailand -- Lower Chao Phraya